POLICE EFFORTS IN HANDLING THE CONFLICT BETWEEN THE LOYAL HEART OF TERATE BROTHERHOOD SILAT COLLEGE AND THE FAITHFUL BROTHERHOOD OF WINONGO IN THE JURISDICTION OF THE MADIUN POLICE - Gilang Ilhami; Karim (Fakultas Hukum Universitas Bhayangkara Surabaya, 2024)
Constitutional Court Decision Number 137/PUU-XIII/2015 and Constitutional Court The Pencak Silat Pencak Silat Brotherhood of Setia Hati Terate and Brotherhood of Setia Hati Winongo in Madiun are in the spotlight because of the conflict that occurred between the two organizations. This conflict raises various security problems in the region. The police's efforts to overcome this conflict were carried out using various strategies, such as a persuasive approach, dialogue and firm action against perpetrators of violence. This research aims to get an overview of the punishment given to members of martial arts schools in Indonesia in general and at large.This research uses empirical methods, or legal research which focuses on how cases will be handled, based on legal provisions or statutory regulations, and then connected to facts or realities that actually occur in society regarding the mitigation efforts that have been carried out by the Madiun Police. The results of this research show the inability of individual members of the silat college to understand the goals and teachings of the Pesilat college, in this case they do not understand and practice the Noble Principles and do not apply the teachings, rules and goals that a silat should have.